Особливості застосування експертних систем - Криворучко, М. О. (ХНУРЕ, 2023)
In the modern world of computer information systems, the development of expert systems is becoming increasingly relevant, since such systems enable a specialist to receive expert advice on any problems that these systems have accumulated knowledge about. Such systems can be used in various fields, which is now very important. Application areas of knowledge-based systems can be grouped into several main classes: control and management, medical diagnostics, fault diagnosis in mechanical and electrical devices, and training. This necessitates consideration of the features of expert systems.
Keywords: експертна система